Community Foundations - The Relevance for Social Funds in Urban Areas : The Tanzania Social Action Fund Experience - Manjolo, Ida (World Bank, Washington, DC, 2012)
This newsletter concerns the relevance for social funds in Urban Areas. Social funds face a common challenge of sustaining the community capacities that are built and investments that are supported beyond the relatively short lifespan of external funding. For long-term sustainability, external funding needs to be replaced by a steady flow of domestic revenue. The Community foundation (CF) approach offers a number of advantages for urban work. Community foundations are independent organizations that provide grants to support a variety of projects identified and implemented by local residents. A CF does not replace the scale of resources and national reach achieved by social funds. But it can provide a partial answer to the sustainability challenge in some large and medium-size urban areas, where it can mobilize local resources and sustain social dynamism and participation in broad areas of development work.